Using an Alternative Trace for QVT - Aranega, Vincent; Etien, Anne; Dekeyser, Jean-Luc (Electronic Communications of the EASST, 2011)
Model transformations are the core of the MDE methodology. They can be expressed using various languages. One of them is QVT, the OMG standard for transformation languages. QVT also provides a traceability mechanism. In general, a trace can be used for many purposes. In this paper, we show the limitations of the trace provided by QVT through different scenarios. Furthermore, based on the QVT language elements, we highlight model transformation concepts that would require consideration. We also propose an alternative trace that takes into account these concepts. It allows us to gather information not provided by the QVT trace and thus fully performs the scenarios. The proposed trace is language independent and can be used without perturbing the QVT transformation execution or the trace generation/exploitation by the engine.